2003
DOI: 10.1002/ppul.10382
|View full text |Cite
|
Sign up to set email alerts
|

Measuring exhaled nitric oxide in infants during tidal breathing: Methodological issues

Abstract: Exhaled nitric oxide (FENO) may provide a tool for identifying infants at risk of developing allergic disease in childhood. In infants there is no standardized collection technique; however, the easiest method is to measure FENO during tidal breathing. In this study we investigated various methodological issues for tidal breathing (TB) FENO in infants. These included the effect of ambient NO, oral or nasal breathing, sedation, and tidal expiratory flow. Furthermore, we compared TB FENO in 88 infants with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
1
50
0
1
Order By: Relevance
“…This would also imply that our study underestimates any differences between groups. However, it has been shown that both nasal and oral NO levels reflect mixed exhaled NO in infants (28) and techniques to avoid nasal contamination of exhaled air in infants require complicated and demanding equipment, unlikely to become useful in practice (30,31). Also, standardization for expiratory flow in infants is technically possible, but difficult (20), and may be unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…This would also imply that our study underestimates any differences between groups. However, it has been shown that both nasal and oral NO levels reflect mixed exhaled NO in infants (28) and techniques to avoid nasal contamination of exhaled air in infants require complicated and demanding equipment, unlikely to become useful in practice (30,31). Also, standardization for expiratory flow in infants is technically possible, but difficult (20), and may be unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Here, measurements based on quiet tidal breathing usually result in higher proportions of children being able to perform the maneuver satisfactorily than spirometry as a forced expiratory maneuver, as illustrated in a review on lung function tests in preschool children with cystic fibrosis (16). Until now, multiple-breath eNO (eNOmb) measurements have mostly been performed in infants and toddlers (17)(18)(19)(20)(21). Despite requiring less cooperation beyond infancy, criteria for standardization of eNOmb measurements are not yet included in the current ERS/ATS guidelines due to methodological issues (9).…”
mentioning
confidence: 99%
“…Variable expiratory flow is problematic due the highly flow dependent nature of FE NO . [27,28] Although the prevalence of recurrent wheezing among infants/toddlers is high, this group of children is heterogeneous. The majority of wheezy infants/toddlers do not have asthma, but rather wheeze for a variety of anatomic and/or pathophysiologic reasons, including but not limited to post-viral airway inflammation and injury, small airway caliber, central airway malacia, or dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…could not perform acceptable tidal breathing FE NO measurements, indicating that unsedated tidalbreathing FE NO may be technically challenging to measure in infants/toddlers. [26] Additional limitations of tidal breathing-FE NO in infants include: potential nasal NO contamination as nasal NO production far exceeds lower airway production, and variable expiratory flow which is problematic due the highly flow dependent nature of FE NO [27,28].…”
Section: Introductionmentioning
confidence: 99%